Values and Power Conflicts in Framing Borders and Borderlands: The 2013 Reform of EU Schengen Governance. Issue 5 (20th October 2019) - Coman, Ramona
ABSTRACT: In recent years, the preservation of the Schengen as a borderland has generated heightened tensions between domestic and European actors. Drawing on a qualitative analysis, this article illustrates how EU institutional actors frame the EU's internal and external borders and how said frames have shaped the EU's Schengen governance. To do so, it scrutinizes the debates that took place from 2011 to 2016 on the reintroduction of internal border controls. The analysis allows us to observe the salience of four frames: the values frame, the conflict frame, the market frame, and the securitization frame. To explain the dynamics of these frames, the article draws on the theoretical arguments of the new intergovernmentalism. The analysis concludes that the framing of borders in European debates is conditioned by the institutional setting of the EU and reflects the spread of the new intergovernmentalism in this policy area.